Application of Unggah-Ungguh Javanese for Moral Values Development in Preschool Children - Hardiyanti, Widya Dwi; Prayitno, Prayitno; Cholimah, Nur; Tjiptasari, Fitriana (FKIP Universitas Lampung, 2025)
Application of Unggah-Ungguh Javanese for Moral Values Development in Preschool Children. Objective: The background that drives this research is the application of unggah-ungguh Javanese can be used as a vehicle for developing character and morals, especially in early childhood. The challenge of moral values in Java includes adapting learning methods that are not by the context of local wisdom. Unggah-ungguh in Javanese society, it is still considered an important thing and even used as a measure to say that someone has good ethics. This study aims to comprehensively analyse the application of the unggah-ungguh Javanese and identify the media and application methods of the unggah-ungguh Javanese in developing morals in early childhood. Methods: This research method used a Systematic Literature Review (SLR) based on PRISMA guidelines to screen and analyse 20 relevant articles from various sources. The article was analysed in depth using a descriptive qualitative method. Data was collected through a literature search of electronic databases, namely Google Scholar, Scopus, Sage, Science Direct, and Taylor & Francis. Findings: Based on the results of the analysis of 20 application articles, unggah-ungguh Javanese, there are 9 articles mentioning findings related to media and methods effective to develop early childhood moral values if using habituation methods such as the habit of saying greetings or simple greetings in Javanese krama inggil (sugeng enjing, sugeng siang, sugeng sonten, sugeng dalu) and using the word manners in Javanese krama inggil (matur nuwun, pangapunten, nuwun sewu, nyuwun tulung). In addition, the application media unggah-ungguh Javanese for children, such as animation video, picture story book, pop-up book, games and traditional Java songs. Conclusion: The application of unggah-ungguh Javanese is one of the effective strategies for instilling early childhood values and morals with habituation from teachers and parents. Collaboration between teachers and parents is necessary to support successful implementation and provide a strong foundation for the child's character in the future. Keywords: early childhood, javanese, moral values, preschool, unggah-ungguh.